Anthropometric indices, but not birth weight, are associated with high blood pressure risk among Malay adolescents in Kuala Lumpur - Bee Koon Poh; Yeow Nyin Ang; Giin Shang Yeo; Yong Zhuan Lee; Shoo Thien Lee; Jasmine Siew Min Chia; Bee Suan Wee (Elsevier, 2022)
Background: With the high prevalence of hypertension, it is important to determine its predictors early. The aim of this study was to determine the association between blood pressure with anthropometric indices and birth weight among a population of Malay adolescents in Kuala Lumpur. Design and methods: This cross-sectional study was carried out among 254 primary and secondary school adolescents aged 10 to 16 years. Anthropometric measurements and blood pressure were determined through standardized protocols, while participants' birth weight was obtained from birth certificate. Body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR) and a body shape index (ABSI) were calculated. Results: Boys had significantly higher weight, height, WC, WHtR and systolic blood pressure (SBP) than girls (p < 0.05). SBP was moderately correlated with body weight (r = 0.60), WC (r = 0.55), BMI (r = 0.54), height (r = 0.47), WHtR (rs = 0.36) and WHR (r = 0.30). Moderate correlations were found between diastolic blood pressure (DBP) with BMI (r = 0.26), WC (r = 0.23) and body weight (r = 0.20). Participants with BMI > +1SD had higher odds of being prehypertensive or hypertensive (aOR 8.97; 95% CI 3.16, 25.48), followed by participants with WC ≥ 90th percentile (aOR 6.31; 95% CI 2.48, 16.01) and participants with WHtR > 0.5 (aOR 5.10; 95% CI 2.05, 12.69). Multiple linear regression showed BMI was positively associated with both SBP and DBP. No significant association was found between birth weight and BP. Conclusion: BMI had the best predictive ability for SBP and DBP. These findings strongly emphasize the importance of primary prevention of hypertension in adolescents, especially among those with high BMI.